Tyrosinase Inhibitory Activity of The Extracts from Garcinia lateriflora Blume var. Javanica Boerl, Garcinia fruticosa Lauterb, and Garcinia xanthochymus - Ambarwati, Neneng Siti Silfi; Elya, Berna (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2024)
Tyrosinase overexpression in humans increases melanin production in the skin, which may have hyperpigmentation-causing effects. In this study, various extracts from the Garcinia lateriflora Blume var. Javanica Boerl, Garcinia fruticosa Lauterb, and Garcinia xanthochymus plants were tested for their ability to inhibit the tyrosinase enzyme. The results showed that the G. fruticosa Lauterb stem bark hexane extract had the highest activity followed succesively by the G. lateriflora Blume var javanica Boerl leaf methanol extract, G xanthochymus mesocarp hexane extract, G. xanthochymus mesocarp methanol extract. The results show that the G. fruticosa Lauterb stem bark hexane extract has the highest tyrosinase inhibitory activity (45.61 ± 1.58%) among the four extracts and the tyrosinase inhibitory activity of kojic acid (65.07 0.86%).